The Role of Chatgpt as A Virtual Assistant in Increasing Student Learning Collaboration - Dara, Chenda; Vann, Rithy; Sok, Vann (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2024)
The rapid development of artificial intelligence (AI) has led to the integration of AI tools like ChatGPT into various sectors, including education. One of the most promising applications is the use of AI as a virtual assistant to enhance student collaboration and learning experiences. Traditional education methods often struggle to foster effective collaboration among students, particularly in large, diverse classrooms. This study aims to explore the role of ChatGPT as a virtual assistant in increasing student collaboration and enhancing the learning process. The primary objective is to evaluate how ChatGPT can assist students in collaborative learning tasks, promote peer interaction, and provide personalized support. A mixed-methods research design was employed, combining qualitative and quantitative data collection methods. The study involved 150 students from different academic disciplines, who were introduced to ChatGPT as a collaborative tool for group projects. Data was collected through surveys, interviews, and collaboration performance assessments. The results indicate that ChatGPT significantly improved student collaboration, with students reporting increased interaction, engagement, and productivity during group tasks. Additionally, ChatGPT’s personalized assistance helped students overcome knowledge gaps and foster a collaborative learning environment. This study concludes that ChatGPT can be an effective virtual assistant in enhancing student collaboration and improving overall learning outcomes, offering valuable insights into AI’s potential in education.